Plant circadian clock control of Medicago truncatula nodulation via regulation of nodule cysteine-rich peptides. (1st December 2021) - Achom, Mingkee; Roy, Proyash; Lagunas, Beatriz; Picot, Emma; Richards, Luke; Bonyadi-Pour, Roxanna; Pardal, Alonso J; Baxter, Laura; Richmond, Bethany L; Aschauer, Nadine; Fletcher, Eleanor M; Rowson, Monique; et al.
Abstract: Legumes house nitrogen-fixing endosymbiotic rhizobia in specialized polyploid cells within root nodules, which undergo tightly regulated metabolic activity. By carrying out expression analysis of transcripts over time in Medicago truncatula nodules, we found that the circadian clock enables coordinated control of metabolic and regulatory processes linked to nitrogen fixation. This involves the circadian clock-associated transcription factor LATE ELONGATED HYPOCOTYL (LHY), with lhy mutants being affected in nodulation. Rhythmic transcripts in root nodules include a subset of nodule-specific cysteine-rich peptides (NCRs) that have the LHY-bound conserved evening element in their promoters. Until now, studies have suggested that NCRs act to regulate bacteroid differentiation and keep the rhizobial population in check. However, these conclusions came from the study of a few members of this very large gene family that has complex diversified spatio-temporal expression. We suggest that rhythmic expression of NCRs may be important for temporal coordination of bacterial activity with the rhythms of the plant host, in order to ensure optimal symbiosis. Abstract : A nodule circadian clock involving the gene Late Elongated Hypocotyl and rhythmic expression of nodule-specific cysteine-rich peptides coordinates waves of metabolic and regulatory activity during symbiosis.